Keterlibatan Warga Terhadap Akun Twitter Pemerintah Provinsi Jawa Tengah, Jawa Timur, Jawa Barat : Analisa Data Mining - Anton Purwadi; Kismartini Kismartini; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2022)
This article focuses on citizen engagement analysis on local government twitter through data mining analysis. Based on the concept of measuring citizen engagement from Haro-de-Rosario in 2018, this article analyzes three official twitter accounts of the Central Java provincial government, East Java province and West Java province. Data were collected by data mining with Scrape Storm software with measurement dimensions consisting of love, reply, retweet, tweet, and followers. The measurement results reveal that the level of citizen engagement varies widely, the highest value of citizen engagement is the account of the province of East Java (0.00068), and the second rank is the province of Central Java with a value of 0.00031 and the third rank is the province of West Java with a value of 0.00023. The design of public communication policies on social media should consider aspects of the level of citizen engagement as a benchmark for government efforts to increase public participation interest in managing local government.